Night school [compact disc, unabridged] : / a Jack Reacher novel - Child, Lee (Child, Lee. Jack Reacher novel., 2016)
It's 1996, and Reacher is still in the army. In the morning they give him a medal, and in the afternoon they send him back to school. That night he's off the grid. Out of sight, out of mind. Two other men are in the classroom--an FBI agent and a CIA analyst. Each is a first-rate operator, each is fresh off a big win, and each is wondering what the hell they are doing there. Then they find out: A Jihadist sleeper cell in Hamburg, Germany, has received an unexpected visitor--a Saudi courier, seeking safe haven while waiting to rendezvous with persons unknown. A CIA asset, undercover inside the cell, has overheard the courier whisper a chilling message: "The American wants a hundred million dollars." For what? And who from? Reacher and his two new friends are told to find the American. Reacher recruits the best soldier he has ever worked with: Sergeant Frances Neagley. Their mission heats up in more ways than one, while always keeping their eyes on the prize: If they don't get their man, the world will suffer an epic act of terrorism.